2016
DOI: 10.1002/pbc.26169
|View full text |Cite
|
Sign up to set email alerts
|

Gliomatosis cerebri: A consensus summary report from the First International Gliomatosis cerebri Group Meeting, March 26–27, 2015, Paris, France

Abstract: Gliomatosis cerebri (GC) is a universally fatal extensive and diffuse infiltration of brain parenchyma by a glial tumor. Many aspects of this phenomenon remain unknown. The First International Gliomatosis cerebri Group Meeting had the following goals: refine the clinical and radiologic diagnostic criteria for GC, suggest appropriate diagnostic procedures, standardize tissue manipulation for histologic and molecular characterization, and prioritize relevant preclinical projects. Also, general treatment recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 34 publications
0
24
1
1
Order By: Relevance
“…5,8 Molecular profiling of DNA methylation and copy number aberrations in 25 human gliomatosis cerebri patients was able to unequivocally assign the cases to known molecularly defined subgroups of nongliomatosis cerebri diffuse gliomas with no evidence for the existence of a distinct gliomatosis cerebri specific molecular subgroup. 7,28 Since gliomatosis cerebri is characterized by the exceptional growth pattern rather than the cell type of the neoplasm, an in vivo diagnosis of gliomatosis cerebri, in contrast to other gliomas, cannot be obtained solely by brain biopsy but requires MRI to evaluate the extent of the lesions and involvement of brain structures. In all dogs examined in this study population, MRI clearly showed that the lesions extended through at least three contiguous cerebral lobes, and therefore fulfilled the criterion used in human medicine for the diagnosis of the entity formerly known as gliomatosis cerebri.…”
Section: Discussionmentioning
confidence: 99%
“…5,8 Molecular profiling of DNA methylation and copy number aberrations in 25 human gliomatosis cerebri patients was able to unequivocally assign the cases to known molecularly defined subgroups of nongliomatosis cerebri diffuse gliomas with no evidence for the existence of a distinct gliomatosis cerebri specific molecular subgroup. 7,28 Since gliomatosis cerebri is characterized by the exceptional growth pattern rather than the cell type of the neoplasm, an in vivo diagnosis of gliomatosis cerebri, in contrast to other gliomas, cannot be obtained solely by brain biopsy but requires MRI to evaluate the extent of the lesions and involvement of brain structures. In all dogs examined in this study population, MRI clearly showed that the lesions extended through at least three contiguous cerebral lobes, and therefore fulfilled the criterion used in human medicine for the diagnosis of the entity formerly known as gliomatosis cerebri.…”
Section: Discussionmentioning
confidence: 99%
“…Tratamentos anti-angiogénicos, como bevacizumab aparentemente não têm eficácia comprovada, o que pode ser explicado devido à reduzida vascularização e ausên-cia de captação de contraste destes tumores. 10 Contudo, recentemente Burger et al, referem que o bevacizumab poderá ser considerado em pacientes com gliomas de padrão maioritariamente infiltrativo.…”
Section: Discussionunclassified
“…In the revised WHO Classification of Tumors of the Central Nervous System (2016), GC is no longer defined as a single entity and several new entities including “diffuse midline glioma with H3 K27M‐mutant” have been introduced 1 . The term “GC,” however, is still used to describe its characteristic growth pattern 2‐4 . As previously reported, GC is neither pathologically nor genetically grouped into a single entity, but most cases share molecular abnormalities commonly found in other gliomas including hot spot mutations and methylation signatures.…”
Section: Figurementioning
confidence: 99%